2009
DOI: 10.1111/j.1442-200x.2009.02865.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology in thalassemia major

Abstract: Children with TM are posed with an increased risk of psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 12 publications
2
26
1
1
Order By: Relevance
“…Beta β‐thalassaemia major and its complications carry a significant psychological impact, causing emotional burden, hopelessness and difficulty with social integration, all of which are more prominent in the adolescence period Thalassaemic adolescents in our study have significantly higher psychosocial morbidity with no difference between boys and girls; Saini et al . also made a similar observation…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Beta β‐thalassaemia major and its complications carry a significant psychological impact, causing emotional burden, hopelessness and difficulty with social integration, all of which are more prominent in the adolescence period Thalassaemic adolescents in our study have significantly higher psychosocial morbidity with no difference between boys and girls; Saini et al . also made a similar observation…”
Section: Discussionmentioning
confidence: 51%
“…Beta β-thalassaemia major and its complications carry a significant psychological impact, causing emotional burden, hopelessness and difficulty with social integration, all of which are more prominent in the adolescence period 20,53,54 Thalassaemic adolescents in our study have significantly higher psychosocial morbidity with no difference between boys and girls; Saini et al also made a similar observation 55 This morbidity is likely to increase with increasing age-, social-and disease-related factors as is evident from our observation of a positive correlation of PSC mean score with duration of illness, regular blood transfusion and DFO transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Literature examining psychological functioning in individuals with thalassemia indicates that this population is vulnerable to experiencing psychological adjustment problems, such as symptoms of depression and anxiety [59]. However, except for one study conducted with adult patients in Italy [7], these studies are generally limited to small, homogeneous samples of children [8,9].…”
mentioning
confidence: 99%
“…A multi center European study reported psychological problems in 47% children (Clemente C et al 2002). In a study of 20 thalassemic and 34 healthy children, it was observed that children with thalassemia were at increased risk of psychopathology (Cakaloz et al 2009). The frequency of psychiatric problems was significantly higher in children with thalassemia (55.0%) as compared to the control group (14.7%).…”
Section: Discussionmentioning
confidence: 96%